Visual search behaviours and verbal reports during film-based and in situ representative tasks in volleyball - Afonso, J.; Garganta, J.; McRobert, A.; Williams M.; Mesquita, I. (European Journal of Sport Science, 2014)
Several researchers have explored the processes underlying perceptual-cognitive expertise, mainly using film-based studies. However, few have compared the extent to which data from film-based settings differ from those obtained through in situ collection. This gap in the literature is a relevant concern, since scientific research is used to provide guidance for designing training programmes. In this paper, eye movement recording and verbal reports of thinking were combined to explore the processes underpinning skilled performance in a representative volleyball task involving both film-based and in situ data collection. Nine volleyball players performed as backcourt defenders while wearing an eye-tracking device and providing verbal reports of thinking after each sequence. A number of significant differences were observed between the data gathered under film-based and in situ conditions. Namely, in the in situ condition participants employed longer fixations (728.11±129.27 ms) than in the film condition (659.57±178.06 ms), and there were differences in the nature of the fixation locations. With respect to verbal reports, participants exhibited superior level of sophistication in the in situ condition (2.57±0.50 vs. 2.30±0.84 in the film condition), while denoting a greater concern with the opponents under this condition (1.00±0.73) than in the film condition (0.59±0.60). These differences emerged despite task design and constraints being highly similar. No differences were apparent in the number of gaze fixations and fixation locations across conditions or in the number of verbalised condition concepts. Although exploratory, our data suggest that the mechanisms underpinning skilled decision-making in sports differ between film-based and in situ conditions.